AI – Powered Learning Disability Detection and Classification System - M. Pragasthi; Ms. N. Vaishnavi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Learning disabilities (LDs) are generally described as a collection of neurological disorders that interfere with an individual’s ability to process and apply knowledge, affecting abilities in reading, writing, and math. To diagnose LDs properly, it is necessary to diagnose them early and accurately, though the traditional approaches used to diagnose them are slow and subjective. This paper discusses the potential of artificial intelligence, especially through machine learning and deep learning methodologies, in enhancing the detection and categorization of LDs. AI may be implemented in educational and healthcare environments to expedite and enhance the accuracy of diagnosis, which would, in turn, accelerate the results in education for people with LDs. This paper outlines the current developments in AI methods for LD identification and the potential they hold for revolutionizing diagnostic and intervention methods.